Musical Dialogue in John Harbison's String Quartet No. 4 - Koay, K. Kheng (Musicologica Olomucensia, 2024)
The study explores different instrumental dialogues that experimented in Harbison's String Quartet No. 4 (2001). Harbison imagines each instrument as an operatic character in the composition. The musical dialogues are presented in different fashions, including between two or more instruments in either confrontation, or with agreeable manners. The piece significantly displays Harbison creatively reintroducing the late 18th century musical dialogue fashion in a new way. Not only is Mozart's and Bach's music the main source of inspiration for Harbison, but also stresses of the off-beats and syncopated jazz fashion are at times heard in the fugal-like imitation passages.
Keywords: John Harbison; Musical Dialogue; 21st century String Quartet